Combinatorial decolorization performance of Pycnoporus sanguineus MUCL 38531 sourced recombinant laccase/mediator systems on toxic textile dyes - Malci, K.; Kurt-Gur, G.; Tamerler, C.; Yazgan-Karatas, A. (SPRINGER, 2023)
Laccases with high redox potential are highly promising for the bioremediation of hazardous textile dyes due to their potential in degrading recalcitrant complex synthetic dyes. In this study, Pslcc2 from white-rot fungus Pycnoporus sanguineus MUCL 38531 was recombinantly produced in Pichia pastoris, and its dye decolorization and detoxification performances on seven textile dyes belonging to azo and triarylmethane dyes were evaluated using combinations of mediators including ABTS, syringaldehyde, and rho-coumaric acid. Moreover, the bioinformatics analyses revealed that Pslcc2 is a high redox potential laccase candidate. Consistently, Pslcc2 showed great potential for decolorization of textile dyes when coupled with a proper mediator at an optimized dye concentration. Pslcc2/ABTS system exhibited 100% decolorization for acid black and malachite green within 4 and 24 h, respectively. The best results for the removal of reactive black (93.2%), crystal violet (90%), basic fuchsin (83.4%), and Congo red (88.2%) were also obtained by Pslcc2/ABTS system within 24 h. Besides, a very efficient decolorization for malachite green (95.6%) was performed by Pslcc2/SA system within 24 h. Attractively, in 5 h, over 60% decolorization for reactive black, crystal violet, and basic fuchsin was achieved by Pslcc2/SA system. Overall, the results revealed the highly remarkable and quick dye removal capacity of Pslcc2/ABTS and Pslcc2/SA systems compared to other laccase/mediator systems reported on corresponding dyes so far. Finally, Pslcc2 could detoxify the toxic dyes such as crystal violet and Congo red into non-toxic products. This study showed that Pslcc2/mediator systems could be eco-friendly solutions for the bioremediation of toxic textile dyes.
Keywords: Bioremediation; Decolorization; Laccase mediator system; Pycnoporus sanguineus recombinant laccase; ABTS; Syringaldehyde; Textile dyes; FUNGAL LACCASE; AZO DYES; EXPRESSION; GENE; DEGRADATION; CLONING; BIOTECHNOLOGY; VISUALIZATION; OXIDATION; INDUSTRY; Environmental Sciences & Ecology